Inaugural Lecture : Applied Energy and Enviroment Past, Present and the Near Future - Mohammad Omar, Abdullah (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Applied Energy refers to any energy conversion when applied to energy systems (Figure 1). It refers primarily to our daily domestic and industrial energy usage and applications in various areas of energy conversion and conservation, energy resources, energy processes, energy storage, safety, and transport, environmental energy pollutants, and sustainable energy systems, as well as techno-economics, energy innovation (Abdullah, 2013).